Implementation of Crossword puzzle Games to Improve SMA Students’ Vocabulary Mastery - Oktofiano Satria Da Cruz; Anselmus Sahan; Benyamin Kau Abi (CV. Samuel Manurung and Co, 2023)
The research subjects were the tenth-grade students and the research area was at SMA DharmaAyu Kefamenanu. This research investigated the improvement of students’ vocabulary by using crossword puzzle games in the classroom. The research design was Classroom Action Research (CAR) conducted in two cycles. The research subjects were 10 of the tenth-grade students of SMA Dharma Ayu Kefamenanu. The data were collected by using observation and vocabulary achievement tests. The collected data were analyzed statistically by using a percentage formula. The students’ average score was 76.5% in pre-test 1 of cycle one; then it was improved to 79.8 % in post-test 1, and increased to 87.5 % in post-test 2 of cycle 2. It indicates that the students’ vocabulary and level of mastery was improved by using crossword puzzle games. This result reminds the teachers of English to use crossword puzzle in teaching and learning process of English, particularly to boost the students’ vocabulary mastery.